The Role of Pericytes in Neurovascular Unit: Emphasis on Stroke - Oztop-Cakmak, Ozgur; Solaroglu, Ihsan; Gursoy-Ozdemir, Yasemin (Current Drug Targets, 2017)
Background: Among the central nervous system (CNS) disorders, diseases like ischemic and hemorrhagic stroke which are important health care problems as well as leading causes for emergency admissions, primarily affect neurovascular structure. Despite their high rate of mortality and morbidity, very few efficient treatment targets have been established until now. Objective: Blood-brain barrier (BBB) is the mostly effected structure in stroke as detected in both clinical studies and experimental settings. BBB is composed of endothelia, astrocyte end-foot, pericytes and basal lamina. Neurovascular unit, pericytes and BBB forming endothelia play significant pathophysiological roles in both ischemic and hemorrhagic stroke. Discussion: In this mini-review, the role of microcirculation and cells of blood-brain barrier in stroke pathophysiology will be discussed with a special emphasis based on pericytes. Pericytes are especially important for providing adequate microcirculatory supply according to needs of neuronal tissue and form one of the functionally important part of BBB and take role in neurovascular coupling. Understanding the role and disease producing mechanisms of neurovascular unit elements in different neurological conditions will provide novel targets for future treatments.
Keywords: no-reflow